Pelatihan Desain Media Pembelajaran Berbasis Aplikasi Powerpoint Interaktif bagi Guru di SDN Inpres 3 Talise Kota Palu - Mailili, Wahyuni H; Hajerina, Hajerina (Jurnal Pengabdian UNDIKMA, 2022)
The purpose of this community service activity is to train on the develop teachers ability in creating Â interactive powerpoint as learning medium for teachers at SDN Â Inpres 3 Talise Palu City, Central Â Sulawesi province. The methods used include lecturing, discussing and practicing. The steps of this community service program are 1) The stage of preparing and developing training materials; 2) Training and ; 3) Mentoring the practice . The results of the implementation of Â the serviceÂ show that there is an in crease in the ability of Â teachers at SDN Inpres 3 Talise Â in developing knowledge, comprehension, professionalism and creativity in designing interactive powerpoint as a medium for learning mathematics in elementary schools.